Strengthening Online Dispute Resolution Justice - Noam Ebner; Elayne E. Greenberg (Washington University Journal of Law & Policy, 2020)
This paper adopts a systems-design approach to focus courts and lawyers on the unexamined: how involving lawyers in the design, development and implementation of court-annexed online dispute resolution (ODR) programs, will strengthen their justice outcomes. The phrase “ODR programs” refers to the new menu of processes for dispute resolution and litigation offered online by courts.
Keywords: online; online dispute resolution; ODR; ODR program; dispute resolution; justice